Treatment of patients with multiple myeloma over 65 yr: more tolerability or better response? - ŞİMŞEK, MELİH; TARKUN, PINAR; Atalay, Figen; Atesoglu, Elif Birtas; Mehtap, Ozgur; Simsek, MELİH; Terzi, Esra; GEDÜK, AYFER; Balli, Fatih; Batman, Adnan; BAYDEMİR, CANAN; Hacihanefioglu, Abdullah (My University, 2015)
ObjectiveTwo-thirds of newly diagnosed patients with multiple myeloma (MM) are over 65yr and/or physically unfit. Such patients are not eligible for high-dose chemotherapy or stem cell transplantation. The treatment aims in these patients should be to prolong survival by obtaining the best possible response, while maintaining good tolerability. The aim of our study was to evaluate the response to treatment and treatment-related toxicities in patients treated with conventional and novel protocols.